A Survey on: Conversion of 2 Dimensional Images to 3 Dimensional Model - Vaidya, Pranoti; Deore, Jyoti; Thakare, Rakhi; Pangavhane, Pooja (International Journal of Computer Sciences and Engineering, 2025)
In this paper we proposed that a system to present an android application for 3Dimentional model construction from 2Dimentional images. The system enables user to have more informative, interactive and user specific experiences with augmented information by recognizing/tracking the content of offline 2D images. For android device which required Low computational power and an image matching technique based on the combination of two binary feature descriptors are applied Our application can be applicable to many areas such as education and entertainment industry.